(untitled) (Natural Resources and Technology, 2020)
Today, a number of data are constantly being generated that require proper processing and access to them. Standard processing techniques could not meet these requirements. The development of information technology and decision theory has contributed to the emergence of the application of modern-applicable methods and approaches for data processing and analysis. The method of data processing from traditional data processing tools is adapted for data processing and with the help of tools and mathematical methods that enable processing and analysis of large data that depend on multiple criteria. This data processing can locate certain problems or shortcomings during the operation, production and management of a company that could not be determined in any other way. Identification and analysis of the problem to be solved, determining the possible solutions to the problem, the criteria according to which the possible solutions are evaluated, i.e. alternatives and the choice of the best possible solution is a decision-making process - (Decision Making - DM), i.e. decision-making process, and as a result of the decision-making process, the decision arises. It is, in fact, the choice of the best of the best possible alternatives to the problem.